1995
DOI: 10.1111/j.1460-9568.1995.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal CGRP Gene Promoter is Inducible by Nerve Growth Factor in Adult Rat Dorsal Root Ganglion Neurons But Not in PC12 Phaeochromocytoma Cells

Abstract: The calcitonin/CGRP gene is transcribed in thyroid C cells and some neuronal cells but not in other cell types. Although the promoter sequences mediating gene activity in thyroid C cells have been extensively studied, the elements responsible for promoter activity in neuronal cells and its stimulation by nerve growth factor (NGF) have not previously been defined. We report the first use of the calcium phosphate procedure to successfully transfect adult rat dorsal root ganglion neurons, which naturally express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
(61 reference statements)
2
15
1
Order By: Relevance
“…Neurotrophins can also influence the cellular expression of neuropeptides such as CGRP, SP, and NPY (e.g., Goedert et al, 1981;Schwartz et al, 1982;Fitzgerald et al, 1985;Lindsay and Harmar, 1989;Wong and Oblinger, 1991 Jones et al, 1994;Mulderry, 1994;Verge et al, 1995;Watson, 1995). It can therefore not be excluded that the changed expression of neuropeptides during aging, or as a result of axotomy, is mediated by changes in the availability of neurotrophins and/or the expression of the neurotrophin receptors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Neurotrophins can also influence the cellular expression of neuropeptides such as CGRP, SP, and NPY (e.g., Goedert et al, 1981;Schwartz et al, 1982;Fitzgerald et al, 1985;Lindsay and Harmar, 1989;Wong and Oblinger, 1991 Jones et al, 1994;Mulderry, 1994;Verge et al, 1995;Watson, 1995). It can therefore not be excluded that the changed expression of neuropeptides during aging, or as a result of axotomy, is mediated by changes in the availability of neurotrophins and/or the expression of the neurotrophin receptors.…”
Section: Discussionmentioning
confidence: 95%
“…With regard to sensory neurons, it has been demonstrated that axonal injury also influences expression of neurotrophin receptors (Verge et al, 1989(Verge et al, , 1992. Moreover, several studies have shown that the expression of a number of neuropeptides such as CGRP, SP, and NPY in sensory neurons can be influenced by neurotrophic factors (e.g., Goedert et al, 1981;Schwartz et al, 1982;Fitzgerald et al, 1985;Lindsay and Harmar, 1989;Wong and Oblinger, 1991;Jones et al, 1994;Mulderry, 1994;Verge et al, 1995;Watson, 1995). Based on these evidences, it has been suggested that the changes in neuropeptide expression seen in sensory neurons following axonal lesions may at least in part be the result of decreased neurotrophic signalling.…”
mentioning
confidence: 96%
“…In the mature nervous system, neurotrophins have been implicated to be important in the balance between growth and retraction of terminal nerve fibers (Purves, 1988;Cowen, 1993), in axonal regeneration after injury (Heumann et al, 1987;Meyer et al, 1992;Funakoshi et al, 1993), and in regulating neuropeptide expression (Goedert et al, 1981;Fitzgerald et al, 1985;Lindsay and Harmar, 1989;Mulderry, 1994;Watson et al, 1995;Verge et al, 1995), as well as neurofilament expression (Gold et al, 1991;Parhad et al, 1995). All of these functions are highly relevant in the complex process of aging (see also introductory remarks).…”
Section: Trk Expression Declines In Aged Primary Sensory Neuronsmentioning
confidence: 97%
“…Furthermore, the MEK1 (mitogenactivated protein kinase/extracellular signal-regulated kinase kinase) inhibitor, PD98059, which blocks the MAPK pathway, inhibited morphine-induced increased expression of CGRP-LI and SP-LI, as well as phosphorylation of ERK and CREB in cultured DRG neurons [70] . Other studies have shown that ERK/MAPK activated CREB in various cell types in vitro [74] and in different brain regions in vivo [75] , and that both CGRP and preprotachykinin gene promoters contain CRE [76][77][78][79] . Thus, chronic morphine exposure appears to enhance the expression of nociceptive sensory neuropeptides such as CGRP and SP via ERK/MAPK pathway and is CREB dependent.…”
Section: Protein Kinase Activationmentioning
confidence: 99%